LAJU PETUMBUHAN CALON INDUK UDANG GALAH POPULASI SINTETIS G1 DARI SUMBER GENETIK YANG BERBEDA - Anny Rimalia; Mukhlisah -; Yulius Kisworo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determin to get potential candidates parental of Giant Freshwater Prawn from genetic material Kintap, Pagatan and Barito of indicator growth. The method used was completely randomized design (6X3) conducted in BBUG Pagatan South Kalimantan. Results obtained the best relative growth ratio from genetic resources Pagatan (Pg) with a value of 157.98% was followed by Br genetic resources relative growth ratio of 132.92% and the latter derived from genetic resources Kintap (Ki) relative growth ratio is 112.23%. Furthermore Average feed conversion ratio from 2,64 to 3,59, with the best conversion value is the genetic source of prawns from Barito. Results of water quality measurements during panelitian still within the tolerance limit for the life of prawns.Keywords: Giant Freshwater Prawn, relative growth ratio and Genetic Resources